Exploring job satisfaction in ftness franchises: a study from a human talent perspective - Salazar-Altamirano, Mario Alberto; Galván Vela, Esthela; Ravina-Ripoll, Rafael; Bello-Campuzano, María Rubí (My University, 2024)
This qualitative study investigates job satisfaction and its impact on the performance of human talent in ftness club franchises in Mexico, based on six semi-structured in-depth interviews conducted in October 2023. The research highlights that internal communication is the primary factor infuencing job satisfaction, followed by interpersonal relationships and organisational climate. These fndings imply that enhancing internal communication and fostering healthy interpersonal relationships can signifcantly improve employee well-being and job performance. The study aims to understand job satisfaction from the human talent perspective, focusing on the factors that afect their satisfaction and performance. The insights gained can inform strategies to improve work life quality and industry efciency in Mexico, serving as a benchmark for future research and a strategic tool for human resource management in similar organisations.
BMC Psychology
Keywords: Job Satisfaction; Fitness Club Franchises; Human Talent; Campus Tijuana